Numerical study of the compressive behavior of concrete material at high strain rate with active confinement. Issue 10 (July 2019) - Ye, Zhicheng; Hao, Yifei; Hao, Hong
It is understood that the lateral inertia confinement, end-friction confinement, and aggregates influence the uniaxial dynamic compressive properties of concrete material. For particular circumstances such as stress wave propagation in concrete generated by impact or blast load on structures, the material is always dynamically loaded with complex stress states. Impact tests on concrete specimens with active confining pressure are often conducted to understand the material behavior under complex stress states for accurate structural analysis in such conditions. However, unlike the uniaxial impact test, the influences of lateral inertia confinement, end-friction confinement, and aggregates on laterally confined impact test have not been studied. This study investigates the properties of concrete materials in split Hopkinson pressure bar tests with confining pressure by means of numerical simulations. Different levels of confining pressures are considered in the simulations. The influences of lateral inertia confinement, end-friction confinement, and aggregates on the test results are studied. It is observed that the contributions of lateral inertia and end-friction confinements to the test results increase with strain rate, but decrease with the confining pressure. The existence of aggregates results in the increase in the dynamic strength of concrete with all levels of confining pressure. The results show that the strain rate effect on concrete dynamic strength decreases with the lateral confinement pressure applied to the specimen. Based on the results from the numerical simulations, empirical relations are proposed to quantify the influences of lateral inertia and end-friction confinement and coarse aggregates on the dynamic compressive properties of concrete material with lateral confining pressures.